Effective drinking water collaborations are not accidental: Interagency relationships in the international water utility sector - Jalba, D.; Cromar, N.; Pollard, S.; Charrois, Jeffrey; Bradshaw, R.; Hrudey, S. (Elsevier, 2014)
The role that deficient institutional relationships have played in aggravating drinking water incidents over the last 30 years has been identified in several inquiries of high profile drinking water safety events, peer-reviewed articles and media reports. These indicate that collaboration between water utilities and public health agencies (PHAs) during normal operations, and in emergencies, needs improvement. Here, critical elements of these interagency collaborations, which can be integrated within the corporate risk management structures of water utilities and PHAs alike, were identified using a grounded theory approach and 51 semi-structured interviews with utility and PHA staff. Core determinants of effective interagency relationships are discussed. Intentionally maintained functional relationships represent a key ingredient in assuring the delivery of safe, high quality drinking water.